EVALUASI DAN PERBAIKAN SISTEM PENGENDALIAN MANAJEMEN PADA KOPERASI BINA MITRA SEJAHTERA PROBOLINGGO - Selvia Sugianto; Bonnie Soeherman (CALYPTRA, 2018)
This research was made to determine the effectiveness and efficiency of management control systems in overcoming employee probloems in Cooperative Bina Mitra Sejahtera Probolinggo. This study used a qualitative approach to obtain a description of the evaluation and improvement of management control systems in the Cooperative. The source of research data came from observations and interviews to the management, chief secretary, and employees of the Cooperative Bina Mitra Sejahtera Proboinggo. The findings of this research indicate that the management control systems can overcome the behavior problem on the employee.